Effect of Delay Separation and Short Term Storage of Serum on Thyroid Stimulating Hormone (TSH) - Basanta Gelal; Subodh Prasad Gupta; Sharad Gautam; Ashwini Kumar Nepal; Binod Kumar Lal Das; Madhab Lamsal; Nirmal Baral (Open Journal of Thyroid Research - Peertechz Publications, 2017)
Introduction: Thyroid stimulating hormone (TSH) regulates the level of thyroid hormones synthesized in the thyroid gland. Its measurement greatly facilitates the clinical diagnosis as well as management of pituitary-thyroid diseases. The level of analytes in biological sample is affected by pre-analytical, analytical and post-analytical factors. Objective: To find the effect of delay separation and short term storage on serum TSH level. Materials and Methods: A total of 15 blood samples were collected from the patients visited to the immunoassay laboratory, Department of Biochemistry, BPKIHS for thyroid function test. Serum TSH was estimated on the day of sample collection, after 24 hours in delay separated samples and after seven days in short-term stored sample by sandwich ELISA method (Eliscan, India). Results: There were no significant difference in median serum TSH in baseline and delay separated samples (1.43 (0.18-6.52) IU/mL, vs 1.61 (0.25-6.51) IU/mL, p = 0.069) as well as baseline and short term stored samples 1.43 (0.18-6.52) IU/mL vs 1.57 (0.26-5.75), p = 0.925).